Concept of Planning, Organizing, Leadership and Supervision in Coverage and Broadcasting Management - Kustiawan, Winda; Zahra, Siti; Sudarmansyah, Halwatia Malika Atsni; Ramadhan, Melja (Lembaga Riset Mutiara Akbar, 2025)
In the era of ever-evolving information, coverage and broadcasting management have an important role in delivering accurate and relevant information. This article discusses the concepts of planning, organizing, leadership, and supervision as the main pillars in media management. Careful planning helps organizations design coverage strategies, while effective organizing ensures resource optimization. Inspirational leadership motivates teams to innovate, while strict supervision maintains quality and compliance with standards. The research method used is library research, with analysis of relevant literature. The results show that success in broadcasting management is highly dependent on the quality of human resources and the ability of leaders to manage resources. This study is expected to provide insight into the application of management in the media industry to improve the effectiveness of reporting in the digital era